Exploring the pros and cons of new approaches for gamete cross-border donation based on fresh and vitrified oocytes - La Marca, A.; Capuzzo, M.; Bartolucci, S.; Schirinzi, F.; Dal Canto, M. B.; Buratini, J. [UNESP]; Renzini, M. Mignini; Rodriguez, A.; Vassena, R. (Universa Press, 2020)
As highlighted by European statistics, the employment of donor oocytes is a growing option for women who cannot make use of their own gametes. As the potential recipients are continuously increasing in number, a donor programme which satisfies this demand is mandatory. Improvements in cryopreservation techniques, like oocyte and embryo vitrification, have led to the overcoming of the sequence of stimulation-retrieval-transfer both from a spatial and a temporal point of view, with the development of cryobanks of oocytes permitting crossborder donation. However, while some studies report comparable success when using vitrified and fresh oocytes we still need to investigate whether the use of fresh oocytes give higher live birth rate than cryop reserved ones, when the same number of oocytes are given. The performance of embryo cryopreservation, conversely, seems to be more reliable. A novel approach based on the shipment of frozen sperm from the recipient's country to the oocyte donor's one, where fresh oocytes are inseminated and the resulting embryos frozen and transported back to the referring IVF centre to perform a frozen embryo transfer may be a good strategy. We believe that the use of frozen embryos from fresh oocytes could be associated with a higher cumulative live birth rate per cycle, while favouring personalised oocyte recipient care with a flexible number of oocytes assigned and limiting the burden of travelling abroad.
Keywords: IVF; oocyte donation; vitrified oocytes; frozen embryos; crossborder